Controlling irregular migration: international human rights standards and the Hungarian legal framework - Gyollai, Daniel (European journal of criminology, 2019)
In the summer of 2015 Hungary constructed a 175 km long barbed-wire fence at its southern border with Serbia. New criminal offences and asylum procedures were introduced that limited access to refugee status determination and ignored agreed EU asylum policy, deterring and de facto preventing asylum seekers from entering Hungarian territory. This paper provides an analysis of these new measures, which criminalized asylum seekers, and the subsequent Hungarian policy in relation to the case law of the European Court of Human Rights – arguing that the Hungarian authorities excessively abused their discretion in implementing these new policies of immigration and border control.